Trends in the Use of Face Coverings in Publicly Accessible Spaces During the COVID-19 Pandemic, King County, Washington, November 2020–May 2021. (September 2022) - Tolentino, Lorenzo; Guthrie, Brandon; Baker, Marissa G.; Beck, Nicola K.; Chan, Nadine; Duchin, Jeffrey S.; Gomez, Anthony; Simckes, Maayan; Wasserman, Cathy; Cohen, Martin A.; Wasserheit, Judith N.
Objectives: Appropriate face covering use at public venues can help mitigate the transmission of SARS-CoV-2 in the absence of widespread vaccination and provide protection when viral variants become more infectious. The objective of this study was to evaluate compliance with a statewide face mask mandate by examining trends in face covering use in publicly accessible spaces in King County, Washington. Methods: From November 27, 2020, through May 11, 2021, we conducted a repeated cross-sectional observational study of face covering use across publicly accessible venues (eg, grocery and convenience stores, airport, transit center, post office). Trained observers recorded perceived sex, estimated age group, and face covering use. We calculated estimates of overall face covering use and prevalence ratios (PRs) with 95% CIs. Results: We observed 9865 people in 53 unique venues during 229 observation intervals during 6 observation periods. Correct face covering use was 87.2% overall and lowest at semi-outdoor venues such as transit hubs (78.1%) and the pick-up curb of Seattle–Tacoma International Airport (69.0%). Correct face covering use was lowest among men (PR = 1.42; 95% CI, 1.27-1.58) and among people aged 2-11 years (PR = 2.74; 95% CI, 2.37-3.17) and 12-17 years (PR = 1.36; 95% CI, 1.07-1.72). Compliance declined among adults aged ≥60 years and among younger age groups before vaccine eligibility. Conclusions: Overall compliance with the statewide face mask mandate in King County was high. Layered mitigation strategies, including but not limited to the use of face coverings, and methods to assess adherence to them are crucial to preventing SARS-CoV-2 transmission.